2022
DOI: 10.1371/journal.pone.0257831
|View full text |Cite
|
Sign up to set email alerts
|

Screen use and internet addiction among parents of young children: A nationwide Canadian cross-sectional survey

Abstract: Objectives To establish the factorial structure and internal consistency of the Internet Addiction Test (IAT) in parents, the level and correlates of problematic internet use, and patterns and types of screen use. Study design Data were collected through an online questionnaire about preconception health among Canadian women and men with ≥1 child. The questionnaire included the IAT and questions about time spent on screens by device type, use of screens during meals and in the bedroom, and perceptions of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Based on previous studies, it is known that parents who spend most of their time using the internet and social media, have been shown to hinder positive communication and interaction opportunities with their children (Dennis et al, 2022). In addition, the role of parents is not only to provide supervision on the use of the internet and social media by their children but how they can process and choose the right health information and from official sources or institutions so that the information read is valid and has trustworthiness (Maeve et al, 2015;Putri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, it is known that parents who spend most of their time using the internet and social media, have been shown to hinder positive communication and interaction opportunities with their children (Dennis et al, 2022). In addition, the role of parents is not only to provide supervision on the use of the internet and social media by their children but how they can process and choose the right health information and from official sources or institutions so that the information read is valid and has trustworthiness (Maeve et al, 2015;Putri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Eight health behaviours were assessed that may increase the risk of adverse reproductive and perinatal outcomes [ 34 ]: (1) frequent alcohol use, (2) any cigarette smoking, (3) cannabis use, (4) low physical activity level, (5) overweight and obesity, (6) poor eating habits, (7) internet addiction and (8) sleeping <6 hours/night. Internet addiction, while not previously identified as a risk factor, was included in an exploratory manner based on emerging evidence suggesting that higher level of device use is associated with maternal depression and poorer relationship satisfaction [ 35 , 36 ]. Frequent alcohol use was defined as alcohol use more than three times per week, measured by “How often do you drink a beverage containing any alcohol?” taken from the PrimeScreen tool described below.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have concluded there is no relation; some have stated that girls have addictive social media use (Cudo et al, 2020), while others state boys spending more screen time (Allen & Vella, 2015;Downing et al, 2017;Munaro et al, 2016;Stald et al, 2014). According to a few studies, mothers use digital media frequently and spend more time on screens (Dennis et al, 2022). This study also analyzed the gender role in screen device consumption patterns with the hypothesis, H4.…”
Section: H1mentioning
confidence: 99%